A2.06 Functional regulatory T-cells in rheumatoid arthritis bone marrow are modulated by IL-15 and strong antigenic stimulation. (24th February 2016) - Massalska, M; Plebanczyk, M; Radzikowska, A; Kuca-Warnawin, E; Prochorec-Sobieszek, M; Musialowicz, U; Skalska, U; Kurowska, W; Kornatka, A; Burakowski, T; Janicka, I; Maldyk, P; et al.
Abstract : Background and objectives: Role of CD4 + Foxp3 + regulatory T cells in control of autoimmune processes, including rheumatoid arthritis (RA) is well proved, however knowledge about Tregs functions in bone marrow (BM) is sparse. As concept of BM active participation in pathogenesis of RA is still developing, in the present work we compared the phenotype of Tregs in paired samples of bone marrow and peripheral blood from patients with RA and osteoarthritis (OA). Impact of IL-15, overexpressed in RA BM, on functional activity of BM Tregs was also investigated. Materials and methods: S amples of BM and peripheral blood were obtained from RA and OA patients during hip replacement surgery. Tregs phenotype was assessed by FACS analysis and immunohistochemical staining. Bone marrow mononuclear cells were cultured with or without IL-15 before functional assays were done (measurement of cells proliferation and cytokines production). Data are shown as mean ± SEM. Results: Treg cells isolated from BM and peripheral blood shared phenotype of memory CD45RO + cells, with significantly higher proportion of activated CD4 + Foxp3 + CD127 + cells and lower proportion of CXCR4 + Tregs in RA BM. Tregs from OA and RA BM as well as from blood of healthy blood donors were functional and suppressed proliferation and cytokines production in coculture with effector T cells. Stronger signal mediated by anti-CD3/CD28 Abs sustained functionality only in RA Treg. After IL-15 treatment, suppression of proliferation by Tregs from OA BM was broken by stronger TCR signal. In contrast, RA Tregs functionality was maintained only when additionally stimulation by anti-CD3/CD28 Abs was supplied (63.3%±6.6%; p = 0.028 and 54.0%±6.1%; p = 0.067 respectively). Despite active suppression RA Tregs pre-stimulated by IL-15 and cultured in presence of anti-CD3/CD28 Abs produced significantly more TNF then Treg from blood of healthy blood donors (42.6 ± 7.4 vs 17.1 ± 5.7; p = 0.028) and OA BM (42.6 ± 7.4 vs 21.0 ± 8.6; ns). Pre-stimulation of the culture by IL-15 did not increase proportion of CD4 + Foxp3 + CXCR4 + in any patients groups. Conclusions: Phenotype and activation status of Tregs present in RA BM are influenced by locally overexpressed IL-15 that finally may contribute to RA pathogenesis, especially in context of TNF production and poor retention of Treg in BM compartment.